High-Grade Cervical Intraepithelial Neoplasia: Impact of Colposcopic Lesion Area on Systemic Immune Responses - Mantoani PTS; Micheli DC; Jammal MP; Vieira JH; Michelin MA; Ferreira CGX; Silva HN; Murta EFC; Nomelini RS (International Journal of Women's Health)
Priscila Thaís Silva Mantoani,1,2 Douglas Côbo Micheli,2 Millena Prata Jammal,2 Julia Hailer Vieira,3 Márcia Antoniazi Michelin,3 Caroline Gabriela Xavier Ferreira,2 Henrique Nascimento Silva,2 Eddie Fernando Candido Murta,2 Rosekeila Simões Nomelini1,2 1Graduate Program in Gynecology and Obstetrics of the Ribeirão Preto Medical School of the University of São Paulo (FMRP-USP), Ribeirão Preto, SP, Brazil; 2Laboratory of Applied Sciences for Women (LaCam)/Department of Gynecology and Obstetrics; Federal University of Triângulo Mineiro, Uberaba, MG, Brazil; 3Research Institute of Oncology (IPON); Discipline of Immunology; Federal University of Triângulo Mineiro, Uberaba, MG, BrazilCorrespondence: Rosekeila Simões Nomelini, Laboratory of Applied Sciences for Women (LaCam)/Department of Gynecology and Obstetrics, UFTM, Av. Getúlio Guaritá, s/n, Bairro Abadia, Uberaba, MG, 38025-440, Brazil, Tel +55 34 3318 5326, Fax +55 34 3318 5342, Email rosekeila@terra.com.brBackground: The progression of high-grade cervical intraepithelial neoplasia (CIN) and cervical cancer is accompanied by a reduction in the immune response. The objectives of the study were to determine whether colposcopic lesion area is associated with serum levels of cytokines IL (interleukin) − 1, IL-6, IL-8, IL-10, IL-12 and TNF-α in precursor lesions of cervical cancer.Methods: The study population comprised patients with high-grade squamous intraepithelial lesion who had undergone colposcopy, cervical biopsy, and measurements of serum cytokines by ELISA (Enzyme-Linked Immunosorbent Assay). Genotyping for HPV (human papillomavirus) 16, 18, 45 and 52 was performed by PCR (Polymerase Chain Reaction). ROC (Receiver Operating Characteristic) curves were calculated to determine whether there existed a cut-off value for serum cytokines in patients with colposcopic lesion area smaller vs larger than 1 cm2. For cytokines with significant results, these cut-off values were used to perform the multivariable analysis.Results: There were 71 patients with CIN 2/3. ROC curves were calculated to verify a cut-off value for serum cytokine levels that could be used to distinguish between lesion areas < 1 cm2 vs ≥ 1 cm2. Values with statistical significance were IL-1 > 13.3 pg/mL and IL-12 ≤ 349.6 pg/mL. In the multivariable analysis, the independent variables associated with colposcopic lesion area greater than 1cm2 were IL-1> 13.3 pg/mL and IL-12 ≤ 349.6 pg/mL [OR (95% CI) = 10.10 (1.50– 67.96); OR (95% CI)=10.70 (1.17– 97.45), respectively].Conclusion: Although CIN 2/3 is a local uterine cervix lesion, there is a systemic immunological response. Our results are unprecedented and could be the target of new important studies in public health and cervical cancer prevention.Keywords: uterine cervical dysplasia, cytokines, uterine cervical neoplasms